How do centres begin the process to prevent contrast-induced acute kidney injury: a report from a new regional collaborative. Issue 1 (2nd September 2011) - Brown, Jeremiah R; McCullough, Peter A; Splaine, Mark E; Davies, Louise; Ross, Cathy S; Dauerman, Harold L; Robb, John F; Boss, Richard; Goldberg, David J; Fedele, Frank A; Kellett, Mirle A; Phillips, William J; et al.
Abstract : Objectives: This study evaluates the variation in practice patterns associated with contrast-induced acute kidney injury (CI-AKI) and identifies clinical practices that have been associated with a reduction in CI-AKI. Background: CI-AKI is recognised as a complication of invasive cardiovascular procedures and is associated with cardiovascular events, prolonged hospitalisation, end-stage renal disease, and all-cause mortality. Reducing the risk of CI-AKI is a patient safety objective set by the National Quality Forum. Methods: This study prospectively collected quantitative and qualitative data from 10 centres, which participate in the Northern New England Cardiovascular Disease Study Group PCI Registry. Quantitative data were collected from the PCI Registry. Qualitative data were obtained through clinical team meetings to map care processes related to CI-AKI and focus groups to understand attitudes towards CI-AKI prophylaxis. Fixed and random effects modelling were conducted to test the differences across centres. Results: Significant variation in rates of CI-AKI were found across 10 medical centres. Both fixed effects and mixed effects logistic regression demonstrated significant variability across centres, even after adjustment for baseline covariates (p<0.001 for both modelling approaches). Patterns were found in reported processes and clinical leadership that were attributable to centres with lower rates of CI-AKI. These included reducing nil by mouth (NPO) time to 4 h prior to case, and standardising volume administration protocols in combination with administering three to four high doses of N-acetylcysteine (1200 mg) for each patient. Conclusions: These data suggest that clinical leadership and institution-focused efforts to standardise preventive practices can help reduce the incidence of CI-AKI.